Nurses perspectives on long‐term condition self‐management: a qualitative study. Issue 1 (January 2016) - Wilkinson, Mandy; Whitehead, Lisa; Crowe, Marie
Abstract : Aims and objectives: This study explored nurses' attitudes, views and beliefs about their role in long‐term condition self‐management. Background: Nurses are well‐placed to assist individuals in long‐term condition self‐management. Yet, there is limited research exploring underlying beliefs of nurses regarding their role in long‐term condition self‐management and how those beliefs may impact on the practice of self‐management. Design: A descriptive, cross‐sectional qualitative design. Participants: A purposive sample of nurses ( n  = 14) working in primary care and secondary care settings in New Zealand. Methods: One focus group and two interviews were conducted. Data were analysed through thematic analysis by the three authors. Results: All nurses interviewed described promoting patient self‐management of long‐term conditions and the approaches they took to do so in practice. The nurses described a strong sense of accountability in relation to their practice. They worked to ensure patient follow‐up and referrals as necessary and described themselves as lynch pins in the management of long‐term conditions. Nurses also recognised that patients would engage at different levels in the self‐management process. However, the sense of accountability did raise a question around the balance between professional accountability and responsibility for the management of the condition and the reality of nurses' ability to work with patients as partners in the self‐management of long‐term conditions. Conclusions: Nurses described both understanding of the importance of promoting patient self‐management but also a strong sense of professional accountability to provide quality care. Nurses recognised that they needed to work to find a balance between these two positions. Relevance to clinical practice: In order for nurses to work as an advocate to support optimal care it is vital that nurses recognise where patient's boundaries and capabilities lie. Nurses are at risk of blurring the boundaries and may not always support people to make choices that promote and/or maintain "self" control (or autonomy) in long‐term condition management.